MANAJEMEN SUMBER DAYA MANUSIA ISLAMI DI SMA NEGERI YANG MENCAKUP KONSEP,PRINSIP,TANTANGAN dan SOLUSI: MANAJEMEN SUMBER DAYA MANUSIA ISLAMI DI SMA NEGERI YANG MENCAKUP KONSEP,PRINSIP,TANTANGAN dan SOLUSI - Reza Aprian Saputra, Kaswadi; Mohamad Iwan Fitriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the implementation of Islamic Human Resource Management (IHRM) in public high schools, focusing on its concepts, principles, challenges, and solutions. IHRM is rooted in values such as justice, trustworthiness, responsibility, professionalism, and deliberation in managing educators and administrative staff. While public high schools must maintain ideological neutrality, universal Islamic values remain relevant in fostering ethical and dignified work culture. This research employs a qualitative approach through literature review, analyzing various policies and theories of Islamic management in education. Key challenges include a lack of understanding among human resources regarding IHRM, secularization stigma in education, and the absence of operational guidelines. Proposed solutions include integrating Islamic values into work ethics, conducting ethics-based HR training, drafting school codes of conduct, and collaborating with IHRM experts. By applying these strategies, public high schools are expected to enhance human resource management that is not only professional but also characterized by integrity, morality, and spirituality